2017
DOI: 10.2527/jas.2016.1290
|View full text |Cite
|
Sign up to set email alerts
|

Surface wetting strategy prevents acute heat exposure–induced alterations of hypothalamic stress– and metabolic-related genes in broiler chickens1

Abstract: Heat stress (HS) is devastating to poultry production worldwide, yet its biology and molecular responses are not well defined. Although advances in management strategy have partially alleviated the negative impact of HS, productivity still continues to decline when the ambient temperature rises. Therefore, identifying mechanism-based approaches to decrease HS susceptibility while improving production traits is critical. Recently, we made a breakthrough by applying a surface wetting strategy and showing that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…insignificant difference of body core temperature monitored continuously between birds raised under either SPRINK or PAD cooled houses over 48 h. In a recent study using broiler chickens, Dridi's group showed that the SPRINK technology reduced body core temperature induced by heat stress by ∼0.5-1 • C (Figure 2A) (31). Similarly, the SPRINK lowered the overall surface temperature than those with dry surface (Figure 2B).…”
Section: Sprinkler Improves Broiler Physiological Parametersmentioning
confidence: 92%
See 1 more Smart Citation
“…insignificant difference of body core temperature monitored continuously between birds raised under either SPRINK or PAD cooled houses over 48 h. In a recent study using broiler chickens, Dridi's group showed that the SPRINK technology reduced body core temperature induced by heat stress by ∼0.5-1 • C (Figure 2A) (31). Similarly, the SPRINK lowered the overall surface temperature than those with dry surface (Figure 2B).…”
Section: Sprinkler Improves Broiler Physiological Parametersmentioning
confidence: 92%
“…AMP, adenosine monophosphate; AMPK, AMP-activated protein kinase; ATP, adenosine triphosphate; HS, heat stress; TN, thermoneutral. Figure 4B was adapted from Rajaei-Sharifabadi et al (31) and used with permission.…”
Section: Sprinkler Improves Water Usage Efficiencymentioning
confidence: 99%
“…RNA integrity and quality was assessed using 1% agarose gel electrophoresis and RNA concentrations and purity were determined for each sample by Take 3 Micro-Volume Plate using Synergy HT multi-mode micro plate reader (BioTek,Winooski, VT). The RNA samples were DNase treated and 1 μg RNA was reverse transcribed using qScript cDNA Synthesis Kit (Quanta Biosciences, Gaithersburg, MD) as we previously described (Rajaei-Sharifabadi H. et al, 2017 ). Real-time quantitative PCR (Applied Biosystems 7500 Real-Time PCR system) was performed as described previously (Rajaei-Sharifabadi H. et al, 2017 ) using 5 μL of 10X diluted cDNA, 0.5 μM of each forward and reverse specific primer, and SYBR Green Master Mix (ThermoFisher Scientific, Rockford, IL) in a total 20 μL reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The RNA samples were DNase treated and 1 μg RNA was reverse transcribed using qScript cDNA Synthesis Kit (Quanta Biosciences, Gaithersburg, MD) as we previously described (Rajaei-Sharifabadi H. et al, 2017 ). Real-time quantitative PCR (Applied Biosystems 7500 Real-Time PCR system) was performed as described previously (Rajaei-Sharifabadi H. et al, 2017 ) using 5 μL of 10X diluted cDNA, 0.5 μM of each forward and reverse specific primer, and SYBR Green Master Mix (ThermoFisher Scientific, Rockford, IL) in a total 20 μL reaction. Oligonucleotide primers used for chicken ATP citrate lyase (ACLY), acetyl-CoA carboxylase alpha (ACCα), fatty acid synthase (FASN), stearoyl-CoA desaturase (SCD-1), malic enzyme (ME), sterol regulatory element-binding protein 1 and 2 (SREBP-1/2), SREBP Cleavage-Activating Protein (SCAP), insulin induced gene 2 (INSIG2), lipoprotein lipase (LPL), hepatic triglyceride lipase (LIPC), adipose triglyceride lipase (ATGL), fatty acid translocase (CD36), peroxisome proliferator-activated receptor alpha and gamma (PPARα/γ), and ribosomal 18S as housekeeping gene were summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation